Similar local order in disordered fluorite and aperiodic pyrochlore structures. (1st February 2018) - Shamblin, Jacob; Tracy, Cameron L.; Palomares, Raul I.; O'Quinn, Eric C.; Ewing, Rodney C.; Neuefeind, Joerg; Feygenson, Mikhail; Behrens, Jason; Trautmann, Christina; Lang, Maik
Abstract: A major challenge to understanding the response of materials to extreme environments ( e.g., nuclear fuels/waste forms and fusion materials) is to unravel the processes by which a material can incorporate atomic-scale disorder, and at the same time, remain crystalline. While it has long been known that all condensed matter, even liquids and glasses, possess short-range order, the relation between fully-ordered, disordered, and aperiodic structures over multiple length scales is not well understood. For example, when defects are introduced ( via pressure or irradiation) into materials adopting the pyrochlore structure, these complex oxides either disorder over specific crystallographic sites, remaining crystalline, or become aperiodic. Here we present neutron total scattering results characterizing the irradiation response of two pyrochlores, one that is known to disorder (Er2 Sn2 O7 ) and the other to amorphize (Dy2 Sn2 O7 ) under ion irradiation. The results demonstrate that in both cases, the local pyrochlore structure is transformed into similar short range configurations that are best fit by the orthorhombic weberite structure, even though the two compositions have distinctly different structures, aperiodic vs. disordered-crystalline, at longer length scales. Thus, a material's resistance to amorphization may not depend primarily on local defect formation energies, but rather on the structure's compatibility with meso-scale modulations of the local order in a way that maintains long-range periodicity. Graphical abstract: Image 1